1988
DOI: 10.1590/s0074-02761988000100013
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the study of simulium and Culicoides of Rio de Janeiro: monthly incidence and biting activity

Abstract: During March 1984 to February 1985, we captured simuliids and biting midges in the National Park of Tijuca, Rio de Janeiro. A study on monthly incidence and biting activity and their correlation to air temperature, relative humidity, and rainfall was made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…However, at Capitán Cáceres none of the climatic variables was statistically significant with re- spect to the fluctuation of the species' densities. Maia-Herzog et al (1988) observed an inversely proportional relationship between the abundance of Culicoides and rainfall, and that neither relative humidity nor mean temperature was correlated with the abundance. These findings are similar to the findings in our study.…”
Section: Resultsmentioning
confidence: 78%
“…However, at Capitán Cáceres none of the climatic variables was statistically significant with re- spect to the fluctuation of the species' densities. Maia-Herzog et al (1988) observed an inversely proportional relationship between the abundance of Culicoides and rainfall, and that neither relative humidity nor mean temperature was correlated with the abundance. These findings are similar to the findings in our study.…”
Section: Resultsmentioning
confidence: 78%
“…Rainfall was also demonstrated as important for the presence of C . insignis [26] in Brazil. These studies demonstrate that climate has an effect on the distribution of Culicoides species.…”
Section: Introductionmentioning
confidence: 99%
“…In Argentina, Aybar et al [25] found that minimum and maximum temperatures and accumulated rainfall were the best indicators of presence of C. insignis and Culicoides paraensis Goeldi. Rainfall was also demonstrated as important for the presence of C. insignis [26] in Brazil. These studies demonstrate that climate has an effect on the distribution of Culicoides spp.…”
Section: Introductionmentioning
confidence: 99%